Ash-Shareef al- Murtadha’s Concept of Speech: A Linguistic Study - Kadhim Abbas, Hamid (Al-Adab Journal, 2019)
This paper studies the concept of speech for Ash-Shareef al- Murtadha who is a fundamentalist, a theologist, and a jurist of Imaamism, and one of the most prominent Imaami figures. The paper falls into five sections where various linguistic issues are discussed, issues such as the concept of speech amongst Ashaai’ris, Mi’tazilis, amd Imaamis, the concept of speech for Ash- Shareef al- Murtadha, discourse and speech, inner thought and speech, role of intention in linguistic reference, linearity of speech, etc. It may be said that most linguistic views of theologists and fundamentalists may be ascribed to religious doctrine bases; however, Arabic traditional studies resulted in views and propositions so essential to modern linguistic research whose views and propositions may not go too far from their traditional counterparts. Specifically, let one consider those associated with the nature of speech as to whether it means the heard utterances and non-contextualised letters, or it means mere signe of real speech that lay behind these utterances.